2021
DOI: 10.3897/zookeys.1054.69075
|View full text |Cite
|
Sign up to set email alerts
|

New species of the genus Inversidens Haas, 1911 (Unionoida, Unionidae, Gonideinae) from Jiangxi Province, China

Abstract: We diagnose and describe a new freshwater mussel species of the genus Inversidens, I. rentianensissp. nov. from Jiangxi Province, China based on morphological characters and molecular data. This paper includes a morphological description and photograph of the holotype, and partial sequences of mitochondrial COI as DNA barcode data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…These regions have the potential to harbour undiscovered, mysterious species. Recent studies conducted in China have revealed new species, thus corroborating this point (Chen et al, 2023;Dai et al, 2023;Wu, Liu, et al, 2021;Wu et al, 2022Wu et al, , 2023.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…These regions have the potential to harbour undiscovered, mysterious species. Recent studies conducted in China have revealed new species, thus corroborating this point (Chen et al, 2023;Dai et al, 2023;Wu, Liu, et al, 2021;Wu et al, 2022Wu et al, , 2023.…”
Section: Introductionsupporting
confidence: 62%
“… Note : Characteristic descriptions of P. capitata , P. sichuanensis , P. yangshuoensis , and P. wuana are referenced from published works (Liu et al., 2023; Wu et al., 2022, 2023). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are three recognized species within this genus, i.e., Inversidens brandtii (Kobelt, 1879), Inversidens pantoensis (Neumayr, 1899), and Inversidens rentianensis Wu & Wu, 2021 [22,23]. I. brandtii is restricted to Japan [21], while I. pantoensis and I. rentianensis are endemic to China [24,25].…”
Section: Introductionmentioning
confidence: 99%